Gustave Le Bon, Rhetoric as Mass Contagion, and 19th Century Rhetoric - Shawn D. Ramsey (Soegijapranata Catholic University, 2017)
In the latest edition of The Present State of Scholarship in the History of Rhetoric, Lynne